Social support and adolescent mental health in Kenya: a parallel mediation analysis of perceived control and gratitude - Zhao, Ming; Miao, Heng; Zhu, Li-Li; Zhang, Xiao-Han; Zang, Li-Wei (Frontiers in Pediatrics, 2025)
IntroductionAdolescent mental health is a global concern. While social support is a known protective factor, the mechanisms through which it impacts mental health, particularly in diverse settings like Kenya, require further exploration. This study aimed to investigate how perceived control and gratitude mediate the relationship between social support and mental health (symptoms of depression and anxiety) among Kenyan adolescents.MethodsA sample of 1,674 adolescents (aged 13–18) from four secondary schools completed validated measures of social support (MSPSS), perceived control (PCS), gratitude (GQ-6), depression (PHQ-8), and anxiety (GAD-7). The data were analyzed using structural equation modeling, controlling for age and gender.ResultsSocial support was directly associated with lower levels of depression (β = −023) and anxiety (β = −023). Social support also positively predicted perceived control (β = 026) and gratitude (β = 049), both of which were, in turn, linked to lower depression and anxiety. Crucially, significant indirect effects were found, demonstrating that social support reduced symptoms of depression and anxiety through the parallel mediating pathways of both perceived control (depression: β = −005; anxiety: β = −004) and gratitude (depression: β = −008; anxiety: β = −006).DiscussionThe findings highlight that perceived control and gratitude are crucial mechanisms through which social support benefits adolescent mental health in Kenya. These psychological resources function as parallel pathways linking social connections to well-being. Interventions should therefore be designed not only to bolster social support systems but also to concurrently cultivate adolescents' sense of personal control and gratitude.